Tuning the Magnetic Anisotropy of Lanthanides on a Metal Substrate by Metal–Organic Coordination (Small 35/2021). Issue 35 (2nd September 2021) - Parreiras, Sofia O.; Moreno, Daniel; Cirera, Borja; Valbuena, Miguel A.; Urgel, José I.; Paradinas, Markos; Panighel, Mirco; Ajejas, Fernando; Niño, Miguel A.; Gallego, José M.; Valvidares, Manuel; Gargiani, Pierluigi; et al.
Abstract : Magnetic Anisotropy The magnetism of lanthanide‐directed nanoarchitectures on surfaces can be drastically affected by small structural changes. In article number 2102753, Sofia Parreiras, Paolo Perna, David Écija, and co‐workers report the effect of the coordination environment in the reorientation of the magnetic easy axis of dysprosium‐directed metal‐organic networks on Cu(111). The authors show that the magnetic anisotropy of lanthanide elements on surfaces can be tailored by specific coordinative metal–organic protocols.